ДОСЛІДЖЕННЯ ГЕНЕРАЦІЇ ОЗОНУ В ІМПУЛЬСНОМУ БАР’ЄРНОМУ РОЗРЯДІ - Блага , О.В.; Божко , І.В. (Інститут електродинаміки НАН України, Київ, 2013)
Researches of generation of ozone by the pulsed barrier discharge were conducted in the wet and the dry atmospheric air, when their absolute humidity were 17 and 0,1 mg/l, respectively. This discharge was realized in chamber with electrode geometry «cylindercylinder» and dielectric barrier with glass. The steepness of voltage pulses that fed on the camera was 0.8 kV/ns, the pulse repetition rate varied in the range 50…800 Hz. The average value of the amplitude of the density current in the discharge reached more than 1,1 A/cm2. The largest concentration of ozone, which was obtained for wet and dry air, made up 16 and 24 mg/l, respectively. The concentration of ozone and the specific energy consumption for his generation almost linearly rose with increased pulse repetition rate. It was shown that the lowest values of the specific energy consumption for generation of ozone in this discharge do not exceed the of 11 and 6 kW · h/kg for the wet and the dry air, respectively. References 10, figures 5.